The Effect of a Pharmacist-Intervention Program on Clinical Outcomes in Diabetes Mellitus Patients - Inasu, Sini T; MV, Kumudavalli; BS, Venkateswarlu (National Journal of Community Medicine, 2023)
Background: Clinical pharmacists are skilled in identifying patient medication-related problems such as adverse drug responses and non-adherence. Pharmacists participate in diabetes management teams and offer direct patient treatment using several practice models in different ambulatory practice settings. The objective is to evaluate the effect of a pharmacist-intervention program on clinical outcomes in diabetes mellitus patients. Materials and methods: The cohort consisted of diabetes patients attending multi-speciality care hospitals. Eligible patients were randomly assigned in a 1:1 ratio to the intervention and control groups. Each patient in the intervention group was counselled by the research pharmacist. The measure of diabetes self-management was assessed using the Summary of Diabetes Self –Care activities (SDSCA) questionnaire. Results: 150 patients out of this population met the inclusion criteria. The study succeeded in proving the effect of pharmacist-led patient education in the improvement of the quality of life and clinical parameters of diabetes. The pronounced differences in the SDSCA scores of the test group and control group signify the impact of interventions and the consistency of the scale as well. Conclusion: The effect of pharmacist-led interventions on diabetic treatment outcomes was evaluated. The results recommend the need for extensive pharmacist-led intervention programs in metabolic disorder management.